Identifying Representative Financial Ratios of The Indian Tyre Industry : A Principal Component Analysis Approach - Jayesh Manjrekar; Akshay Dilipkumar Damani (The Indonesian Journal of Accounting Research, 2023)
Financial Ratio analysis is a quintessential technique to evaluate financial statements and is widely used to interpret the performance of companies. This paper examines the application of factor analysis to financial ratios. Factor analysis is applied to investigate and find representative ratios based on different business functions and stakeholder perspectives to reduce complexities in analyzing financial performance through ratio analysis due to multiple ratios. Companies from the Indian tire industry listed on the Bombay Stock Exchange (BSE) have been selected for the study. A form of factor analysis is Principal component Analysis (PCA). From an initial set of fifty-three ratios, nine factors were generated, of which the ratios based on the highest factor loading were identified and selected as the representative ratios. Multiple regression analysis was carried out to eliminate statistically insignificant variables, which helped eliminate twenty ratios. Once again, factor analysis was deployed on the remaining variables, which generated seven factors as the outcome. Factors were named, and representative ratios were identified. Cluster analysis was performed to validate the results of factor analysis. The study shows that it is not essential to compute multiple ratios to assess the financial performance of companies.